Coverage of the lower third of the limb and foot injuries using reverse sural fasciocutaneous flap described by Carriquiry - Camila Garcia Sommer; Aluísio Marino Roma; Lauro Arnoldo Ferreira Koehler; Cristiane Camargo Ferreira; Verena Benedick Coimbra; Antonio Roberto Bozola (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Skin grafts are not effective to cover lesions in the distal third of the lower limbs that expose the bones, joints, tendons, and blood vessels due to a limited vascular bed and poor granulation of the wounds. These lesions can only be corrected with microsurgical transfer or muscle, myocutaneous, or fasciocutaneous flaps. Methods: The lower border of the flap was marked 5 cm above the malleolus. The upper border was marked after providing sufficient length for complete coverage of the lesion. The incision was performed at the marked upper border, and the skin and subcutaneous tissue were elevated together with muscle fascia. The sural nerve was preserved in its original bed. The flap was lifted to the marked lower border (the pedicle). At this point, the flap was transposed at a sufficient angle to cover the lesion. Results: Eight cases of surgery were conducted using the flap described above. All cases had exposed bones and tendons in the distal region of the limb, back of the foot, or both, in which the reverse sural fasciocutaneous flap with the technique proposed by Carriquiry was used. The cases showed satisfactory esthetic and functional results. Conclusion: The used flap can correct lesions of the lower third of the limbs and foot. It is relatively easy to make, with good vascular supply, and there is no functional loss of the donor area.